The biliodigestive anastomosis with defunctional loop: technical aspects - Delgado, B; Praderi, Raúl; Crespo, L (Cirugía del Uruguay, 2020)
Various features of bile duct-digestive anastomosis with dysfunctionalized loop, aimed at suppression of blackflow regarded as causing angiocholitis, are considered. Different types of dysfunctionalized anastomoseis,· with their advantag,e-s and shortcomings, are discussed. A series of 29 cases is surveyed.